An Argentine in The Warburg. Humanismo y exilio en la obra de Héctor Ciocchini - Bollig, B (Universidad Nacional del Litoral, 2024)
The emblem was a key subject of study for the Bahía Blancan poet and humanist Héctor Ciocchini for a large part of his career as a research. The Warburgian tradition plays a central role here, in particular Aby Warburg’s concept of Pathosformelm, or forms of pathos. Our intention is to study the critical essays of Ciocchini and a selection of relevant poems in order to trace this presence of Warburg and his tradition, as well as the role of England more generally, to sketch a particular model of humanism, and to offer a contribution to the reconstruction of the Warburg school in Argentina. Of particular importance is the presence of exile, the practical context of a large part of Ciocchini’s critical and poetic work, researched and writing in London during an important period in his life in the 1970s and 80s.